Application of the space-for-time substitution method in validating long-term biomass predictions of a forest landscape model. (August 2017) - Ma, Jun; Xiao, Xiangming; Bu, Rencang; Doughty, Russell; Hu, Yuanman; Chen, Bangqian; Li, Xiangping; Zhao, Bin
Abstract: Validation of the long-term biomass predictions of forest landscape models (FLMs) has always been a challenging task. Using the space-for-time substitution method, forest biomass curves over stand age were generated from a forest survey dataset (FSD) in the Lesser Khingan Mountains area ( LKM ), Northeastern China and compared with long-term biomass predictions of LANDIS-II model. The results showed that mean forest age and mean biomass of the LKM in 2000 were 51.6 years and 84.2 Mg ha −1, respectively. Significant linear correlations were found between FSD derived biomass and simulated biomass in the aggradation phase for the entire LKM and most subregions. However, a considerable difference in the mean maximum biomass (53.45 Mg ha −1 ) existed between from FSD and simulation during the post-aggradation phase. The space-for-time substitution method has potential in validating time series biomass predictions of FLMs in aggradation phase when only limited forest inventory data is available. Highlights: Space-for-time substitution method to create age-based biomass dynamics. Validation of LANDIS-II model at site, subregional, and landscape scales. Consistency between simulated biomass and forest survey dataset derived biomass.